Simulation of Thermal Transfer Attributes Under Varying Magnetic Fields Strain Influences and Viscous Energy Dissipation - Dukru, Dovine; Deka, Bhaskarjyoti; Dey, Bamdeb; Bora, Abhijit (Zielona Góra: Uniwersytet Zielonogórski)
This study investigates the mathematical modeling of impermeable fluid motion that conducts electricity, focusing on the effects of magnetism and chemical interactions on thermal energy, mass transfer, viscosity dissipation, and Soret-Dufour phenomena. These interactions are vital for advancements in technology, geophysical sciences, and biology, particularly in magnetohydrodynamics (MHD). The research describes the governing equations for momentum and energy conservation under varying magnetic fields and performs a numerical analysis of flow behavior influenced by viscous dissipation on a semi-infinite surface.
Keywords: thermal energy and mass; chemical interaction; dissipation of viscosity; degree of stretch; varying magnetic field